Determinación de la importancia del e-commerce en los servicios hoteleros de 3, 4 y 5 estrellas de la ciudad de Iquitos - Hidalgo Gonzales, Raul Benjamin (2023)
Developed the thesis: "Determination of the importance of e-commerce in hotel services of 3, 4 and 5 stars in the city of Iquitos.", It has been determined that hotel services require greater technological innovation, the need to open a more option in electronic businesses to achieve a better technological impact and thus, improve or introduce e-commerce in companies; tourism companies can capture a greater tourist flow with a loyal brand and a change of attitude from the management or senior management to the lodging buttons. The applied method was from a quantitative approach and applied research, described the situation of e-commerce in tourism companies; the non-experimental descriptive study design, with a population of 64 hotels and sample in 31 hotels of 3, 4 and 5 stars. The Survey was used as a data collection instrument with various assessments such as binary or dichotomous responses, multiple alternatives and satisfaction according to the Likert scale. The Spss 25 statistic was used to obtain the results, with which the findings were discovered. 18 assessments have been studied, obtaining results according to the type of question and alternatives; Finally, the hypothesis that e-commerce is significantly important to improve the tourist flow in the 3, 4 and 5 hotel stars services of the Iquitos city was demonstrated.